(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective:To determine the functional outcome of traumatic brachial plexus injuries managed in our institution with our own designated treatment protocol( Hand and Upper Limb Surgery-HULS). Methods:This descriptive study was conducted in Hand and Upper Limb Surgery center CMH Lahore Medical College from 12th October 2012 to 12th October 2020.Patients of either gender and all ages with traumatic brachial plexus injuries fulfilling the inclusion criteria were assessed and treated with our own designitated algorithm (HULS protocol). Post treatment functional results were gradded as excellent, good, fair and poor. Results:The total number of patients in our study were 336.Mean age was 32.72 ± 5.58 years.Male patients were 316(94%) and female 20(5.9%). Right sided brachial plexus injury was noted in 245(72.9%) patients and left in 91(27%).Mean follow up peroid was 18 months(range 12 to 23 months).Post treatment functional results were excellent in 16(4.7%) patients, good in 159(47.3%),fair in 121(36%) and poor in 40(11.9%) patients. Conclusion:Traumatic brachial plexus injuries managed as per HULS protocol resulted in excellent and good functional outcome in majorityof our patients.We found this protocol relevant, applicable and feasible with improved clinical decision making, patient care and outcomes in traumatic brachial plexus injuries.